2013
DOI: 10.1007/s11605-012-2025-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Perforation in Non-Faeculant Diverticular Peritonitis—Incidence and Clinical Significance

Abstract: A proportion of patients with non-faeculant peritonitis have a persistent perforation which is associated with a poorer outcome and is likely to result in failure of a non-resectional management strategy. Updated classification systems and tailored peri-operative investigations are required to identify this sub-group of patients and improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Of note, the management of acute diverticulitis has undergone substantial change in recent years. This has largely been driven by advances made in interventional radiological techniques, improved surgical techniques and the availability of improved antibiotic therapies [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the management of acute diverticulitis has undergone substantial change in recent years. This has largely been driven by advances made in interventional radiological techniques, improved surgical techniques and the availability of improved antibiotic therapies [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…it is noteworthy that our overall morbidity of 25% is not low; nevertheless, only 7 patients presented severe complications, which included the 5 failures requiring re-exploration and resection, and no patients in the series died. 24 in our experience, although a hydropneumatic test allowed us to identify 3 patients with an unsuspected perforation and exclude them from lavage, there were 5 failures of the initial treatment that required reoperation and resection. 21 however, despite being a randomized trial, there was some selection bias, because, as the authors stated very honestly, 52 patients were not assessed for eligibility because of surgeon preference.…”
Section: Discussionmentioning
confidence: 78%
“…Taken together, these clinical and imaging findings identify patients at high risk of failure of conservative management and indicate a persistent perforation, which is defined as a histologically proven perforation present within the surgically resected specimen. One study observed that in patients who underwent operative management for acute diverticulitis with peritonitis, a perforation identified histologically was associated with increased morbidity, length of stay in hospital, physiological score and operative severity score . A persistent perforation could explain the high rates of treatment failure after laparoscopic lavage for acute perforated diverticulitis where persistent and recurrent intra‐abdominal sepsis occur due to peritonitis and ongoing abscess formation, translating into higher reoperation rates and increased mortality …”
Section: Discussionmentioning
confidence: 99%
“…One study observed that in patients who underwent operative management for acute diverticulitis with peritonitis, a perforation identified histologically was associated with increased morbidity, length of stay in hospital, physiological score and operative severity score. 20 A persistent perforation could explain the high rates of treatment failure after laparoscopic lavage for acute perforated diverticulitis where persistent and recurrent intra-abdominal sepsis occur due to peritonitis and ongoing abscess formation, translating into higher reoperation rates and increased mortality. 21 Therefore, every effort should be made to distinguish patients with acute perforated diverticulitis who have generalized peritonitis requiring an emergency operation and those who do not have generalized peritonitis, and may be managed conservatively.…”
Section: Discussionmentioning
confidence: 99%